The Rainfall Market - Yu, Yŏng-gwang (Ace, 2025)
"If you could swap your life for a better one, which would you choose? On the outskirts of Rainbow Town, there is an old, abandoned house. They say that if you send a letter detailing your misfortunes there, you could receive a ticket. If you bring this ticket to the house on the first day of the rainy season, you'll be granted entrance into the mysterious Rainfall Market-where you can choose to completely change your life. No one is more surprised than Serin when she receives a ticket. Lonely and with no real prospects for a future, Serin ventures to the market, determined to create a better life for herself. There, she meets a magical cat companion named Issha and they search through bookstores, perfumeries, and magical realms while Serin tries to determine what her perfect life will look like. The catch? Serin only has one week to find her happiness or be doomed to vanish into the market forever. And all the while, a shadow follows quietly behind them..."--